The influence of brand awareness, brand image, and customer loyalty on purchasing decisions for Apple brand products - Ariel, Bobie Manfred Alfaro Dick Bradley; Siagian, Valentine; Malau, Harman (Institute of Computer Science (IOCS), 2024)
This study was conducted to examine the effect of Brand Awareness, Brand Image, and Customer Loyalty on Purchasing Decisions. This research was conducted by looking at how each of these factors individually and together influence consumer decisions to buy Apple brand products. The method used in this research is the survey method and this research uses a quantitative approach. The population in this study is every consumer who uses Apple brand products or goods in Indonesia. In this study, data collection was obtained by purposive sampling with sample criteria being consumers who have worked and a minimum education level of S1, then distributing questionnaires online via google form with a Likert scale directly to 115 consumers in Indonesia and using the SPSS version 29 application tool. In this study, data analysis used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, Hypothesis Test and finally the Coefficient of Determination Test. The results showed that Brand Awareness, Brand Image, and Customer Loyalty simultaneously had a significant influence on Purchasing Decisions. Further results that Brand Image and Customer Loyalty have a positive and significant influence on Purchasing Decisions, while Brand Awareness shows a positive but insignificant influence. Of the three independent variables studied, Customer Loyalty shows the strongest influence on Purchasing Decisions, followed by Brand Image and Brand Awareness.